Waxing Effect on the Physical Attributes, Antioxidant and Sugar Contents of Orange (Citrus sinensis L. osbeek) Stored at Room Temperature in Nigeria - Adetuyi, FO; Ibrahim, TA; Ajalia, Lola; Oloye, DA (Bangladesh Journal of Scientific and Industrial Research, 2010)
The objective of this work was to determine the influence of edible wax and non-edible wax on the physical attributes, vitamin C and total phenol of orange stored at room temperature (28±5°C) in Nigeria. The oranges were divided into three lots, viz one was waxed with sheabutter, the second with petroleum wax and the third was left unwaxed. They were subsequently analyzed for physical apperance, weight loss, vitamin C and total phenol. The waxed orange had a better appearance and market appeal than the unwaxed orange. The percentage weight loss in unwaxed orange 5.88% was higher than significantly (P0.05) higher in waxed than the unwaxed orange at every sampling point while there was no significant (P0.05) difference in the total phenol of both waxed and unwaxed orange. It is concluded that oranges should be waxed with sheabutter because it had better qualities than unwaxed and pertoleum waxed orange and also to prevent postharvest losses in these orange. Key words: Waxed; Unwaxed; Orange; Vitamin C; Phenol DOI: 10.3329/bjsir.v45i2.5707 Bangladesh J. Sci. Ind. Res. 45(2), 111-116, 2010